The impact of accelerated learning in the english language learning process in ninth graders at Centro Escolar Dr. Doroteo Vasconcelos, year 2015. - Beltrán Lizama, Guillermo Armando
The first factor is that the English teaching at Dr. Doroteo Vasconcelos School has a deficiency because the English teachers are not updated with the right tools to teach their students. Second, they do not have access to the computer lab, tape recorders and so on because the school does not even have a tape recorder, so the students never listen to authentic audio materials. They just listen to the teacher’s pronunciation which is not really good because when they listen to other people or foreigners; they get confused because of the accent. Besides that, the third factor is that at Dr. Doroteo Vasconcelos School some students go to study there because their parents send them not because they want to. They are not motivated at all, for that reason they might show attitude when the teacher is telling them to study or do something in the classroom.